2020
DOI: 10.26637/mjm0801/0018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting physico-chemical properties of octane isomers using QSPR approach

Abstract: Topological indices are very important parameters in the QSPR study. In this paper a novel topological index named as RS 2-index has been introduced. Further, we carry QSPR analysis for the set of octane isomers. The QSPR study reveals that the performance of RS 2-index is better than the M 1 (G), M 2 (G), M 1 (G) and M 2 (G).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The results compensate for the lack of chemical and medical testing and serve as a theoretical framework for pharmaceutical engineering by determining the number of topological indices. The QSPR modeling of antituberculosis drugs is detailed in [ 20 ] completed the QSPR study of octane isomers and found a best-fit model for it. Earlier studies on covid-19, blood cancer, anti-cancer, and QSPR different TIs for various chemical structures motivate us much.…”
Section: Methodsmentioning
confidence: 99%
“…The results compensate for the lack of chemical and medical testing and serve as a theoretical framework for pharmaceutical engineering by determining the number of topological indices. The QSPR modeling of antituberculosis drugs is detailed in [ 20 ] completed the QSPR study of octane isomers and found a best-fit model for it. Earlier studies on covid-19, blood cancer, anti-cancer, and QSPR different TIs for various chemical structures motivate us much.…”
Section: Methodsmentioning
confidence: 99%
“…These topological indices are useful for determining relationships between a molecular compound's structure and its physicochemical proper-ties [18]. The total surface of polychlorophenyles was assessed to calculate with the aid of a symmetric division index in [8]. The heat of the formation of an alkane is best predicted using the augmented Zagreb index in [6].…”
Section: Methodsmentioning
confidence: 99%
“…The heat of the formation of an alkane is best predicted using the augmented Zagreb index in [6]. For more understanding visit the subsequent articles [4,9,19,[26][27][28][29][30][31]. Various regression methods using TIs were implemented for the QSPR and QSAR [5].…”
Section: Methodsmentioning
confidence: 99%
“…Further, Sourav Mondal et al [24] introduced six new neighbourhood degree sum indices, namely, N D 1 , N D 2 , N D 3 , N D 4 , N D 5 and N D 6 . Many researchers are working on the QSPR analysis of various molecules [3,18,8,10,11,15,16,17,23,24,25,26,33,31,32,34], since it is an economically efficient mechanism to test compounds instead of testing them in a wet lab. Moreover, QSPR analysis can be used to develop models that can forecast properties or activities of organic chemical substances.…”
Section: Introductionmentioning
confidence: 99%